Academic Performance (CGPA) Influences Mental Health: A Study of Students at Seremban Medical Assistant College (SMCA) - Bakri, Nur Hani Syazwani; Mat Razi, Nur Aisyah Nabilah; Ahmad, Mohd Firdaus; Safwan, Nur Syazwani Zulaikha; Dahlan, Nur Dalilah; Mokhtar, Ummi Kalthum (Information Management and Business Review, 2024)
Medical students, especially in Malaysia, face many challenges due to their field of study and expectations of their profession. It is widely acknowledged that medical courses are among the hardest academic pursuits. In Malaysia, medical students must undergo a five-year undergraduate program, continuing with a clinical rotation and practical experience to sharpen their knowledge and skills. Despite the awareness given, the stigma of mental health persists, leading medical students to hesitate in seeking help out of fear of being perceived as weak. The study identifies whether mental health influences academic performance (CGPA) among medical students at Seremban Medical Assistant College (SMCA). This study used a quantitative method, and a questionnaire was distributed to 215 respondents. The data were analyzed using the Statistical Package for Social Science (SPSS). It was found that there were significant areas where CGPA influenced the mental health of SMCA medical students. Specifically, it was observed that as CGPA increased, there was a corresponding decrease in mental health among the students. This shows that the students are experiencing mental health issues due to their responsibility to maintain a good academic performance in their field of study. In addition, this study offers valuable insight to health practitioners and students on the importance of maintaining mental health and helps in raising awareness.